Gut bacterial microbiome composition and statin intake-A systematic review - Andreia M. Dias; Gonçalo Cordeiro; Maria M. Estevinho; Rui Veiga; Luis Figueira; Marta Reina‐Couto; Fernando Magro; the Clinical Pharmacology Unit, São João Hospital University Centre (Wiley, 2020)
Abstract Recently, the gut microbiome has become an important field of interest. Indeed, the microbiome has been associated to numerous drug interactions and it is thought to influence the efficacy of pharmacologic treatments. Although statins are widely prescribed medications, there remains considerable variability in its therapeutic response. In this context, we aimed to investigate how statins modulate the gut microbiome and, reversely, how can the microbiome influence the course of anti‐hypercholesterolemic treatment. We conducted a systematic review by searching four online databases, in accordance with PRISMA guidelines. Studies addressing gut microbiome changes following statin treatment and those assessing statins' response and associating it with patients' microbiome were included. Due to the limited number of results, we decided to include studies enrolling both humans and animals. We summarized information from three human and seven animal studies and aimed to assess the influence of gut microbiome composition on statin response (Outcome 1) and to evaluate the impact of statin treatment on the gut microbiome (Outcome 2). An association between a certain microbiome composition that promoted the lipid‐lowering effect of statins was found. However, what kind of microorganisms and how they can exert this effect remains uncertain. Furthermore, statins might have a role in the modulation of the gut microbiome, but then again, it is still unknown whether this change is directly caused by the drug or another metabolic mechanism. Even though gut microbiota may have several potential therapeutic implications, its use as a personalized predictive biomarker requires further studies.